Karakterisasi Genetik Tempuyung (Sonchus arvensis L.) Berdasarkan Penanda Molekuler Sequence-Related Amplified Polymorphism - Subositi, Dyah; Mujahid, Rohmat (JURNAL BIOLOGI INDONESIA, 2013)
Tempuyung (Sonchus arvensis L.) is known as an important medicinal plant used as a diuretics andantihypertensives. This plant is widely distributed in Indonesia. Genetic diversity of tempuyung is importantinformation as a database for further research especially in medicinal plant standardization. The objective of thisstudy was to analyse genetic characterization of tempuyung based on SRAP (Sequence-related amplifiedpolymorphism) molecular markers. Thirteen samples were collected from 8 different locations and amplified using5 primer SRAP combinations. Similarity matrix was calculated using Dice coefficient. Unweighted Pair GroupMethod Using Arithmetic Mean (UPGMA) cluster analysis was performed to develop a dendrogram. The resultindicates that there was a genetic variation among tempuyung accessions and divided into 4 clusters with similarityindex of 0,7719. Citeureup and Turen3 accessions were the most closely similar with similarity index of 0,8936. Inconclusion, SRAP markers may serve as an efficient and effective tools to analyze the genetic diversity amongtempuyung accessions.Keywords: genetic characterization, tempuyung (Sonchus arvensis L.), SRAP